Modeling and simulation for fatigue life analysis of robots with flexible joints under percussive impact forces. (February 2016) - Nie, Songliang; Li, Yuwen; Shuai, Guo; Tao, Song; Xi, Fengfeng
Abstract: This paper presents a method for modeling and analyzing the fatigue life of robots with flexible joints, with a particular focus on applications under percussive impact forces. This development is motivated by growing interests in robotic automation for operations with percussive impact tools. The most important characteristic of percussive operations is the repetitive impacts generated by the tool, such as a percussive rivet gun. After modeling of a flexible joint robot, a forced vibration solution is provided by including the impact forces generated by the percussive gun, projecting them onto the robot joint space and treating them in terms of the Fourier transform. As a result, the joint angular displacements can be solved using a standard vibration method. Then the joint stresses can be determined through Hooke's law. To consider the stress variations caused by the robot operating at different poses using different rivets, a multiple-loading fatigue model is applied from which an equation is derived to determine the total number of the rivets that can be riveted before robot's fatigue failure. Based on simulation using our model, the following observations are received. First, the joint torsional stresses vary with robot's position and orientation. Second, no joint will always experience the maximum stress and the joint stress dominancy also varies with robot's position and orientation. Third, at a given riveting point, the rivet gun direction considerately affects the joint stresses. Fourth, the fatigue life of each joint is different; therefore robot's fatigue life should be evaluated based on the shortest joint fatigue life. Highlights: A method is presented for modeling and analyzing the fatigue life of robots with flexible joints, with a particular focus on applications under percussive impact forces. A multiple-loading fatigue model is applied to determine the total number of the rivets that can be riveted before robot's fatigue failure. Based on simulation using our model, four observations are received and the fatigue life can be evaluated.